How does the Perceived Ethicality of Corporate Services Brands Influence Loyalty and Positive Word-of-Mouth? Analyzing the Roles of Empathy, Affective Commitment, and Perceived Quality - Markovic, Stefan (Journal of business ethics, 2018)
In the past few decades, a growth in ethical consumerism has led brands to increasingly develop conscientiousness and depict ethical image at a corporate level. However, most of the research studying business ethics in the field of corporate brand management is either conceptual or has been empirically conducted in relation to goods/products contexts. This is surprising because corporate brands are more relevant in services contexts, because of the distinct nature of services (i.e., intangible, heterogeneous, and inseparable) and the key role that employees have in the services sector (i.e., they can build or break the brand when interacting with customers). Accordingly, this article aims at empirically examining the effects of customer perceived ethicality in the context of corporate services brands. Based on data collected for eight service categories using a panel of 2179 customers, the hypothesized structural model is tested using path analysis. The results show that, in addition to a direct effect, customer perceived ethicality has a positive and indirect effect on customer loyalty, through the mediators of customer affective commitment and customer perceived quality. Further, employee empathy positively influences the impact of customer perceived ethicality on customer affective commitment, and customer loyalty positively impacts customer positive word-of-mouth. The first implication of these results is that corporate brand strategy needs to be aligned with human resources policies and practices if brands want to turn ethical strategies into employee behavior. Second, corporate brands should build more authentic communications grounded in their ethical beliefs and supported by evidence from actual employees.